Evidence of proactive forefoot control during landings on inclined surfaces - Morey Klapsing, G.; Arampatzis, A.; Brüggemann, G. P. (Journal of Motor Behavior, 2007)
The notion of proactive control of landings is generally accepted, and some underlying mechanisms have already been described. Only little is known on adjustments at the foot level, however. The authors therefore investigated the foot and ankle behavior of 24 participants as they landed on differently inclined surfaces. A 4-segment model of the foot and ankle provided 3-dimensional kinematics. They also analyzed activation patterns from several muscles and the ground reaction force. Participants anticipated the different surfaces, as shown by the forefoot kinematics and the activation patterns before touch down. Anticipation of the surface inclination led to adjustments in forefoot orientation and probably also in joint stiffness. The authors suggest that those adjustments tend to enhance the self-stabilizing potential of the mechanical system. The enhancement of that potential would ease the subsequent stabilization, reducing the demands on the neural system.